Adaptive prediction of a class of stochastic processes - Azarskov, V. M.; Zhiteckij, L. S.; Sushchenko, O. A. (Problems of Informatization and Control, 2005)
The problem of the asymptotically optimal prediction of some stochastic processes described by difference equations whose parameters are known is considered. To solve this problem, a simple adaptive estimation algorithm is proposed and analyzed. The asymptotical properties of this algorithm are established. The simulation results are given